Hubungan antara Kecerdasan Emosional dengan Perilaku Konsumtif pada Bintara Remaja DIT Samapta Polda Sumatera Selatan - Dwi Andika; Mutia Mawardah (Kuras Institute, 2022)
Adolescence is a period that is very easily controlled by emotions and sometimes has outbursts, which arise due to conflicting values. Teenagers tend to be unstable so in deciding something, especially in consumptive behavior, they tend to be controlled by emotions. These passionate emotions are sometimes difficult for both teenagers and their parents or adults around them. The benefit of this research is the hope that it can provide an overview and references to psychology, especially for social psychology. The purpose of this study was to determine the relationship between emotional intelligence and consumer behavior in adolescents. The research method used is descriptive with a quantitative approach. The population taken by the researcher was the Junior Officer of the Directorate of Samapta Polda in South Sumatera. The technique in taking samples used is purposive sampling. The total sample is 250 Junior Officers at the Directorate of Samapta Polda in South Sumatera. Before conducting the research, the researchers carried out an experiment on a scale or too (Try Out) to 104 Youth Officers at the Directorate of Samapta Polda in South Sumatera, while the remaining 146 were samples in the study. The conclusion is that there is a very significant relationship between emotional intelligence and consumptive behavior among the Youth Officers of the South Sumatra Regional Police's Samapta Directorate.